The right to proof and its legal configuration within the General Organic Code of Processes - García-Díaz, José (2023)
The right to proof, understood as that evidentiary activity recognized in favor of the parties, has special relevance within the general theory of the process, which is why the constitution has decided to recognize it as a constitutional law as an integral part of the right to due process. Despite its importance, the right to proof has not deserved adequate treatment by the Constitutional Court, being legally associated as a part of the macro right to due process, thus ignoring the vast substantial content that it should enjoy. In contrast, within Spanish and Colombian comparative law, it is evident that through the right to proof, two dimensions or edges are manifested that combine not only mere access or opportunity to present evidence, but also the application of well-founded evidentiary limits, as well as the conception of the right to proof with an average system of administration of justice. This article aims to shed light on those forgotten or unknown dimensions of the right to proof, as well as its application by judges when justifying the acceptance or not of a certain request for access to evidence required by the parties.